Microcontroller Based Soil Fertility and PH Meter Design - Al Ayyuby, M. Sholahuddin; Sujono, Sujono; Munawarah, Munawarah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to design and build a soil pH and fertility measuring device based on a microcontroller. Fertile soil is crucial for plant growth, and one of its indicators is soil pH. This device is designed to help farmers understand the quality of their soil, especially in areas less accessible to modern technology. The methods used in this research include hardware and software development. A pH sensor, soil moisture sensor, and temperature sensor are used to measure relevant parameters. The data obtained is displayed via an OLED LCD and can be accessed wirelessly using the ESP32, which serves as the main processor. The results of this research indicate that the developed device can provide accurate information regarding soil pH and fertility. By using this device, farmers can better understand their soil conditions, which in turn can improve agricultural yields. This research also aims to stimulate public interest in microcontroller technology and its applications in agriculture, as well as to contribute positively to increasing agricultural productivity in rural areas.